2010
DOI: 10.1186/1756-9966-29-137
|View full text |Cite
|
Sign up to set email alerts
|

Shenqi fuzheng, an injection concocted from chinese medicinal herbs, combined with platinum-based chemotherapy for advanced non-small cell lung cancer: a systematic review

Abstract: BackgroundPlatinum-based chemotherapy has been a standard therapy for advanced non-small cell lung cancer (NSCLC), but it has high toxicity. In China, Shenqi Fuzheng, a newly developed injection concocted from Chinese medicinal herbs has been reported that may increase efficacy and reduce toxicity when combined with platinum-based chemotherapy, but little is known about it outside of China. The aim of this study was to systematically review the existing clinical evidence on Shenqi Fuzheng Injection(SFI) combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 13 publications
2
61
0
Order By: Relevance
“…The traditional functions of both Radix Codonopsis and Radix Astragali are in enhancing immune function (Cho and Leung, 2007;Chan et al, 2008;Zhang et al, 2010). Some other previous studies have also demonstrated that SFI exhibited anti-tumor synergy effects accompanied by chemotherapy in tumor-bearing murine model and clinical application (Dai et al, 2008;Dong et al, 2010;Zhu et al, 2010), some of which have shown that SFI may play an important role in chemotherapy, such as improving quality of life, tumor response, performance status, and reducing the toxicity of chemotherapy. However, the in vivo efficacy of SFI on immunological effector cells, which play a key role against tumor growth under immunosuppression, is poorly understood.…”
Section: Introductionmentioning
confidence: 87%
“…The traditional functions of both Radix Codonopsis and Radix Astragali are in enhancing immune function (Cho and Leung, 2007;Chan et al, 2008;Zhang et al, 2010). Some other previous studies have also demonstrated that SFI exhibited anti-tumor synergy effects accompanied by chemotherapy in tumor-bearing murine model and clinical application (Dai et al, 2008;Dong et al, 2010;Zhu et al, 2010), some of which have shown that SFI may play an important role in chemotherapy, such as improving quality of life, tumor response, performance status, and reducing the toxicity of chemotherapy. However, the in vivo efficacy of SFI on immunological effector cells, which play a key role against tumor growth under immunosuppression, is poorly understood.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, herbs used in Traditional Chinese Medicine (TCM) are gaining wider recognition in recent years as an underexploited source for potential therapeutic compounds (4,5). Matrine ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2015; 9(1): 16-34. increasing complete remission and partial remission efficacy rate, and decreasing adverse events such as nausea, vomiting, oral mucositis, and leucopenia. Moreover, Shenqi fuzheng injection intervention appeared to be useful to increase efficacy and reduce toxicity when combined with platinum-based chemotherapy for advanced non-small-cell lung cancer (NSCLC) and colorectal cancer (12,70). In addition, the combination of concurrent chemoradiotherapy with Shenqi fuzheng injection in patients with head and neck neoplasms could effectively enhance immunity with the levels of CD3, CD4, and CD4/CD8 increased, improve quality of life, and decrease adverse events such as nausea, vomiting, oral mucositis, skin lesions, and leucopenia (71).…”
Section: Wwwbiosciencetrendscommentioning
confidence: 99%